A study of the acquisition of discourse markers by Chinese learners of English - Bu, Jiemin (International Journal of English Studies, 2013)
This study investigates the acquisition of discourse markers by Chinese learners of English in terms of gender, style and individual identity. The subjects of the study are 15 female university students and 15 male university students. The data is collected by means of audio recording in the classroom discussion and in the interviews. The examined discourse markers are like, yeah, oh, you know, well, I mean, right, ok and actually , and a total of 1292 tokens for these discourse markers are identified in the subjects’ classroom discussion and interviews. The results of the study show that: (1) the female subjects use discourse markers more frequently than the male subjects. (2) all the subjects employ discourse markers in the interviews at a higher rate than in the classroom discussion. (3) the subjects’ individual identity has the effects on their use of discourse markers. (4) the subjects display their individual variations in their frequencies of discourse markers in the interviews and in the classroom discussion respectively.